2006
DOI: 10.1111/j.1472-765x.2006.01980.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture conditions for the production of haloalkaliphilic thermostable protease from an extremely halophilic archaeon Halogeometricum sp. TSS101

Abstract: Aims: Isolation and screening of extreme halophilic archaeon producing extracellular haloalkaliphilic protease and optimization of culture conditions for its maximum production. Methods and Results: Halogeometricum sp. TSS101 was isolated from salt samples and screened for the secretion of protease on gelatin and casein plates containing 20% NaCl. The archaeon was grown aerobically in a 250 ml flask containing 50 ml of (w/v) NaCl 20%; MgCl 2 1%; KCl 0AE5%; trisodium citrate 0AE3%; and peptone 1%; pH 7AE2 at 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 25 publications
2
44
0
1
Order By: Relevance
“…Whole haloarchaeal cells have been used for the degradation of organic pollutants and in the treatment of concentrated textile waste waters, particularly the first dye bath liquor from the dying process, which contains a high salt load (Margesin and Schinner 2001), but only few studies have been reported on their enzymes. Thus, few biochemical studies have been carried out with amylases (Good and Hartman 1970;Pérez-Pomares et al 2003 or proteases (Vidyasagar and Prakash 2006) from haloarchaea. These enzymes could keep high activity and stability in high salt environments and could have potential application value.…”
Section: Enzymes For Industrymentioning
confidence: 98%
“…Whole haloarchaeal cells have been used for the degradation of organic pollutants and in the treatment of concentrated textile waste waters, particularly the first dye bath liquor from the dying process, which contains a high salt load (Margesin and Schinner 2001), but only few studies have been reported on their enzymes. Thus, few biochemical studies have been carried out with amylases (Good and Hartman 1970;Pérez-Pomares et al 2003 or proteases (Vidyasagar and Prakash 2006) from haloarchaea. These enzymes could keep high activity and stability in high salt environments and could have potential application value.…”
Section: Enzymes For Industrymentioning
confidence: 98%
“…Halophilic archaea have a wide range of temperature preferences depending upon the nature of adaptation and salt requirements (Wejse et al, 2003). Most halophilic archaea and their enzyme production have rather high temperature optima, in the range between 35 and 50°C (Shand and Perez, 1999;Vidyasagar et al, 2006). In this study, Nnm.…”
Section: Effect Of Initial Ph and Incubation Temperature On Hadh Prodmentioning
confidence: 99%
“…The commonly used organic components included casamino acid, yeast extract and tryptone (Oren, 2006). In addition to medium components, the initial pH of the cultivation medium and the incubation temperature were found to play an important role in enzyme production (Vidyasagar et al, 2006). Another problem typically encountered in fermentation is the contamination of fermentation mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable attention has been focused on enzymes of moderately halophilic bacteria, since they have substantial biotechnological potential (29,56). While several proteases from extreme halophiles, members of the halophilic archaea, have been characterized (12,15,19,36,44,49,50,51,57), fewer proteases from moderately halophilic bacteria have been purified and studied in depth (9,14,18,20,21,33).The moderately halophilic bacterium Pseudoalteromonas ruthenica CP76 was isolated from a saltern located in Isla Cristina (Huelva, Spain). This strain was selected for its ability to produce an extracellular protease, haloprotease CPI, which has a molecular mass of 38.0 kDa (46, 47).…”
mentioning
confidence: 99%